2015
DOI: 10.1016/j.dcn.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Short-term test–retest reliability of resting state fMRI metrics in children with and without attention-deficit/hyperactivity disorder

Abstract: To date, only one study has examined test-retest reliability of resting state fMRI (R-fMRI) in children, none in clinical developing groups. Here, we assessed short-term test-retest reliability in a sample of 46 children (11-17.9 years) with attention-deficit/hyperactivity disorder (ADHD) and 57 typically developing children (TDC). Our primary test-retest reliability measure was the intraclass correlation coefficient (ICC), quantified for a range of R-fMRI metrics. We aimed to (1) survey reliability within and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 69 publications
3
59
0
Order By: Relevance
“…Second, this research was conducted in healthy, non-adolescent individuals. Variance between subjects may change slightly in different populations, e.g., clinical or adolescent populations, which can affect the calculation of reliability; for example, test-retest reliability has been shown to differ between ADHD and normal populations (Somandepalli et al, 2015). However, this is not expected to change the estimate of site effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this research was conducted in healthy, non-adolescent individuals. Variance between subjects may change slightly in different populations, e.g., clinical or adolescent populations, which can affect the calculation of reliability; for example, test-retest reliability has been shown to differ between ADHD and normal populations (Somandepalli et al, 2015). However, this is not expected to change the estimate of site effects.…”
Section: Discussionmentioning
confidence: 99%
“…There are many test‐retest reliability studies on the static FC. For example, it has been suggested that the test‐retest reliability of the static FC is fair‐to‐good when examined in both region‐ [Wang et al, ] and voxel‐wise manners [Shehzad et al, ; Somandepalli et al, ], and the static FC‐based brain network properties are still satisfactorily reliable [Andellinia et al, ]. However, there are few test‐retest reliability studies on dynamic FC or dynamic FCT.…”
Section: Discussionmentioning
confidence: 99%
“…These short-term best-case reliability estimates yielded moderate-to-high values. Still, for most indices, controls were significantly more reliable than patients in some brain regions (100). These preliminary findings highlight the importance of examining longer-term (i.e., one week) test-retest reliability across ages (beyond the one small study documenting test-retest reliability in children (101)), by sex, and in each clinical condition-of-interest as part of the foundational work required to build a scientific edifice.…”
Section: Principal Measures and Approachesmentioning
confidence: 92%
“…In this regard, R-fMRI has a ways to go (but see the Consortium on Reliability and Replicability dataset for a novel resource (99)). In ADHD, one study examined short-term (intra-session) test-retest reliability of four R-fMRI indices (ALFF and fractional ALFF, ReHo, and FC of posterior cingulate cortex (PCC), a core DMN node) (100). These short-term best-case reliability estimates yielded moderate-to-high values.…”
Section: Principal Measures and Approachesmentioning
confidence: 99%